2018
DOI: 10.1103/physreva.98.052705
|View full text |Cite
|
Sign up to set email alerts
|

Ion survival in grazing collisions of H with vicinal nanosurfaces as a probe for subband electronic structures

Abstract: We study the electron dynamics at a monocrystalline Pd(111) surface with stepped vicinal nanostructures modeled in a simple Kronig-Penney scheme. The unoccupied bands of the surface are resonantly excited via the resonant charge transfer (RCT) interaction of the surface with a hydrogen anion reflected at grazing angles. The interaction dynamics is simulated numerically in a quantum mechanical wave packet propagation approach. Visualization of the wave packet density shows that, when the electron is transferred… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…This may be due to the fact that the textured surfaces are modifying the energies of the band gap, the surface state and the image states represented by the parameters of the pseudopotential we are using to model. It was found in our previous publication [13] that the distance d between vicinal steps is one important surface structure property that effects the position of the modulation peaks. As mentioned earlier, D cl = 1 a.u.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…This may be due to the fact that the textured surfaces are modifying the energies of the band gap, the surface state and the image states represented by the parameters of the pseudopotential we are using to model. It was found in our previous publication [13] that the distance d between vicinal steps is one important surface structure property that effects the position of the modulation peaks. As mentioned earlier, D cl = 1 a.u.…”
Section: Resultsmentioning
confidence: 97%
“…Results for a particular vicinally stepped surface, therefore, should modify based on these three parameters as was shown in Ref. [13]. However, the comparison of vicinal RCT among various metals, the focus of the present study, will partly borrow from their flat-substrate properties as will be shown.…”
Section: B Wave Packet Propagationmentioning
confidence: 95%
See 3 more Smart Citations